Treating a Viral Culture: Using Cultural Competency and Social Informatics to Design Contextualized Information Literacy Efforts for Specific Social Information Cultures - Simons, Rachel N.; Elkins, Aaron J. (The Usage and Impact of ICTs During the Covid-19 Pandemic, 2023)
This chapter proposes a novel theoretical framework, Social Information Cultural Competency (SICC), that may be used for designing contextualized information literacy efforts. The SICC approach leverages the frameworks of social informatics, cultural competency, and psychosocial understandings of information behavior to encourage information professionals to develop more nuanced understandings of specific social information cultures. After defining this approach, the chapter then applies the SICC framework to a case study considering information literacy interventions addressing a social information culture engaged in sharing COVID-19 misinformation through social media. As part of this case study, the chapter discusses three current information literacy approaches to COVID-19 online misinformation interventions: inoculation or "prebunking" efforts, accuracy prompts before posting or sharing, and online conversation groups. Finally, the SICC framework is compared with each of the three current approaches. The chapter concludes with implications of this novel framework for current and future information literacy efforts aimed at combatting dis/misinformation within social information cultures.